Acousto−Optics: Recent Studies and Medical Applications - Mohammadreza Omidali; Ali Mardanshahi; Mariella Särestöniemi; Zuomin Zhao; Teemu Myllylä (Biosensors, 2023)
Development of acousto−optic (AO) techniques has made progress in recent years across a range of medical application fields, especially in improving resolution, detection speed, and imaging depth. This paper presents a comprehensive overview of recent advancements in AO−based techniques that have been presented after the previously published review in 2017. The survey covers a description of theoretical modeling strategies and numerical simulation methods as well as recent applications in medical fields. It also provides a comparison between different techniques in terms of complexity, achieved depth in tissue, and resolution. In addition, a comparison between different numerical simulation methods will be outlined. Additionally, a number of challenges faced by AO techniques are considered, particularly in the context of realistic in vivo imaging. Finally, the paper discusses prospects of AO−based medical diagnosis methods.